Coke formation in the co-production of hydrogen and phenols from pyrolysis-reforming of lignin. (8th September 2022) - Li, Xianglin; Liang, Jingyi; Zhang, Lijun; Zhang, Shu; Xu, Leilei; Wang, Yi; Hu, Xun
Abstract: The phenolics derived from pyrolysis of lignin are important fractions of bio-oil, which could be reformed to generate hydrogen. Nevertheless, some phenolics are value-added chemicals and they might not have to be utilized as source of hydrogen. In this study, we have explored the concept of co-production of hydrogen and phenolics via a pyrolysis-reforming process at the low to medium temperatures of 450–650 °C over Ni/Al2 O3 catalyst. The results indicated that, below 500 °C, pyrolysis of lignin was almost the exclusive reaction route to form phenolics of varied side chains. The effective reforming of the phenolics initiated at 600 °C and became remarkable at 650 °C. Meanwhile, cracking of the methoxy group and other side chains of the phenolics was also intense at these higher temperatures, producing phenol as the main phenolic compound. Polymerization of the phenolics on Ni/Al2 O3 catalyst occurred from 450 to 650 °C, while the gasification of the precursors of coke accelerated at 650 °C, forming remarkably lower amount of coke together with enhanced yield of hydrogen. The coke formed from the phenolics was generally the polymeric type with abundant aliphatic structures like C–O–C, –OH and -C-H, low thermal stability, low carbon crystallinity, hydrophilic surface and amorphous morphology at 450–650 °C. The polymerization or cracking of the phenolics could form multiple carbon layers in the vicinity of nickel species, and also on alumina. Graphical abstract: Image 1 Highlights: Pyro-reforming of lignin for co-production of H2 and phenolics is investigated. Cracking side chains of phenolics to phenol occurs in parallel with reforming. Polymerization of phenolics takes place to a higher extent at 450–550 °C. Coke is polymeric with low thermal stability/crystallinity and hydrophilic surface. Polymerization/cracking of phenolics forms multiple carbon layers in vicinity of Ni.